If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13(x + -7) = -7 + -6 Reorder the terms: 13(-7 + x) = -7 + -6 (-7 * 13 + x * 13) = -7 + -6 (-91 + 13x) = -7 + -6 Combine like terms: -7 + -6 = -13 -91 + 13x = -13 Solving -91 + 13x = -13 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '91' to each side of the equation. -91 + 91 + 13x = -13 + 91 Combine like terms: -91 + 91 = 0 0 + 13x = -13 + 91 13x = -13 + 91 Combine like terms: -13 + 91 = 78 13x = 78 Divide each side by '13'. x = 6 Simplifying x = 6
| -8+2=-14-8 | | 9=-3(4c+1) | | -34+25x=9x^2+38 | | 5(x-8)+26=-9 | | -32+z=-7.4 | | 12-20x=4x | | (6x+8)=(5x+7) | | .5n+3=7 | | -3(5s-2)-6=-3(8s+7)-3 | | -32+2=-7.4 | | x+2x+3x+(3x-2)=97 | | 15x=19-45 | | x-0.4=2.9 | | -3(3s-1)-3=-2(8s+7)-2 | | 15x=19+45 | | 3(4x+2)=16x+2-4x+4 | | 8x+7-7x=16 | | -1-3(5k+7)=-3k+38 | | 10x+25x-9=7(5x+8) | | 6x+3(x-20)=62-x+2 | | 11x-4+4x-11+51-3x=180 | | 2=2(u+4)-8u | | 12x-4=3(4x+6) | | 6(-6)+7=13+7(-6) | | -4x-4x=71-7 | | -2y+4=6 | | 7.77x+49=60.3729+7x | | 2(2k-11)=4(K-2) | | 8+4r-5=9r+18-2r | | x=1/.390625 | | (10x-28)=(6x) | | x+5=-2x+8-4x |